Effects of sidestream tobacco smoke on P53 expressions in Rattus novergicus tongue epithelial mucosa - Dian Angriany; Diah Savitri Ernawati; Adiastuti Endah Parmadiati; Hening Tuti Hendarti; Rosnah Binti Zain (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2019)
Background: Smoking, both active and passive, has been widely recognised as toxic to the human body, since it induces several forms of cancer, including that affecting the oral cavity. Benzopyrene, the carcinogen contained in tobacco smoke, can even lead tocarcinogenesis which potentially affects the regulation of cell apoptosis in both active and passive smokers. Purpose: This study aims to investigate the carcinogenic effects of cigarette smoke on apoptosis of rat tongue mucosae through p53 expression. To determine the risk of malignant transformation through tumor suppressor genes in the apoptotic pathway. Methods: Rattus norvegicus subjects were divided into four groups, namely Treatment Group 1 exposed to sidestream cigarette smoke for four weeks (P1), Treatment Group 2 exposed to sidestream cigarette smoke for eight weeks (P2), Control Group not exposed to sidestream cigarette smoke for four weeks (K2), and Control Group (K) not exposed to sidestream cigarette smoke for eight weeks (K2). The exposure process was conducted using a smoking pump and alternating exposure. Four micron-thick sections of formalin were subsequently fixed together with paraffin embedded biopsy material from tongue mucosa of Rattus norvegicus. The tissue sections from the treatment groups were then analyzed immunohistochemically to compare the expressions of p53 and Bcl-2 proteins with those of the control groups. Results: The T-test results indicated statistically significant differences in the expressions of p53 between the 4-week control group (K1) and the 4-week treatment group (P1) (p=0.01, p<0.05) as well as between the 8-week control group (K2) and the 8-week treatment group (P2) (p=0.03, p<0.05). Conclusion: Exposure to cigarette smoke can induce changes in tumor suppressor genes and also affect the regulation of cell apoptosis, thus changing cell structure and leading to malignancy.